OPTIMALISASI LIMBAH PARAS PUTIH MELALUI DIVERSIFIKASI PRODUK INTERIOR - Kadek Risna Puspita Giri; I Gusti Ayu Canny Utami; Freddy Hendrawan (Universitas Mercu Buana, 2023)
Saka Bali Arts, as one of the home-based woodcarving industries in Singapadu Village, Gianyar Regency, Bali, has a potential to process white sandstone residue into artworks. Using sandstone as the main base material, Saka Bali Arts produces 1.4 cubic to 2 tons monthly of sandstone residue. Normally, this is disposed of or used as landfill material for building construction or sent to other vendors to produce artworks like small sculptures and reliefs with simpler shapes, depending on the customer's demand. However, producing processed white sandstone residue received little attention from producers and consumers. This situation resulted in the lack of diversified artwork products displayed on the storefront. The main reasons are the lack of local artisans' skills to produce different kinds of products from sandstone residue and the lack of a marketing development strategy, so the market reach of processed sandstone residue is unexploited. Hence, efforts are needed to develop more specific interior products and a product diversification strategy through product recycling to increase long-term sales. Another way to support this is by optimizing branding and marketing to expand marketing. This study uses the methodology of Murdjito (2022) in the form of stages carried out in the implementation of community service activities. In the long term, we expect Saka Bali Arts to become a model for similar home-based industries in optimizing white parasite stone material residues through increased product innovation, sales, and profitability.